Clinical Molecular and Genomic Epidemiology of Morganella morganii in China - Xiang, Guoxiu; Lan, Kai; Cai, Yimei; Liao, Kang; Zhao, Mei; Tao, Jia; Ma, Yi; Zeng, Jianming; Zhang, Weizheng; Wu, Zhongwen; Yu, Xuegao; Liu, Yuyang; et al. (Frontiers in Microbiology, 2021)
Objectives Ongoing acquisition of antimicrobial resistance genes has made Morganella morganii a new clinical treatment challenge. Understanding the molecular epidemiology of M. morganii will contribute to clinical treatment and prevention. Methods We undertook a six-year clinical molecular epidemiological investigation of M. morganii from three tertiary hospitals in China since 2014. Antimicrobial susceptibility testing was performed using a VITEK-2 system. All isolates were screened for β-lactam and plasmid-mediated quino-lone resistance genes by PCR. Isolates carrying carbapenem-resistant genes were subjected to whole-genome sequencing (WGS). The variation and evolution of these mobile genetic ele-ments (MGEs) were then systematically analyzed. Results Among all M. morganii isolates (n=335), forty (11.9%) were recognized as multidrug resistant strains. qnrD1, aac(6')-Ib-cr, blaTEM-104 and blaCTX-M-162 were the top four most prevalent re-sistance genes. Notably, phylogenomic and population structure analysis suggested clade 1 (rhierBAPS SC3 and SC5) associated with multiple resistance genes seemed to be widely spread. WGS showed a blaOXA-181-carrying IncX3 plasmid and a Proteus genomic island 2 var-iant carrying blaCTX-M-3, aac(6')-Ib-cr coexisted in the same multidrug resistant strain zy_m28. Additionally, a blaIMP-1-carrying IncP-1β type plasmid was found in the strain nx_m63. Conclusions This study indicates a clade of M. morganii is prone to acquire resistance genes, and multidrug resistant M. morganii are increasing by harboring a variety of MGEs including two newly dis-covered ones in the species. We should be vigilant that M. morganii may bring more extensive and challenging antimicrobial resistance issue.